Chronically Implanted Microelectrodes Cause c-fos Expression Along Their Trajectory - Pflüger, Patrick; Pinnell, Richard C.; Martini, Nadja; Hofmann, Ulrich G. (Frontiers in Neuroscience, 2020)
When designing electrodes and probes for brain–machine interfaces, one of the challenges faced involves minimizing the brain-tissue response, which would otherwise create an environment that is detrimental for the accurate functioning of such probes. Following the implantation process, the brain reacts with a sterile inflammation response and resulting astrocytic glial scar formation, potentially resulting in neuronal cell loss around the implantation site. Such alterations in the naïve brain tissue can hinder both the quality of neuronal recordings, and the efficacy of deep-brain stimulation. In this study, we chronically implanted a glass-supported polyimide microelectrode in the dorsolateral striatum of Sprague–Dawley rats. The effect of high-frequency stimulation (HFS) was investigated using c-fos immunoreactivity techniques. GFAP and ED1 immunohistochemistry were used to analyze the brain-tissue response. No changes in c-fos expression were found for either the acute or chronic stimulus groups; although a c-fos expression was found along the length of the implantation trajectory, following chronic implantation of our stiffened polyimide microelectrode. Furthermore, we also observed the formation of a glial scar around the microelectrode, with an accompanying low number of inflammation cells. Histological and statistical analysis of NeuN-positive cells did not demonstrate a pronounced “kill zone” with accompanying neuronal cell death around the implantation site, neither on the polymer side, nor on the glass side of the PI-glass probe.